An experimental study of the structural capacity of rectangular beam under flexural test – rice husk concrte (0%, 10% & 12% replacement) - Muhammad Zul Hazmi, Mansor (2019)
The production of cement consumes natural resources, apply high energy and produce high amounts of greenhouse gases. It cause almost to 7 % of the global carbon dioxide emissions, as the production of one ton of ordinary Portland cement releases one ton of carbon dioxide. Nowadays the major issue is the environmental effects and the health effects which increasing from days to days. Because of that, the utilization of green concrete in construction must be applied widely as the alternatives for the conventional concrete and due to the benefits of the usage of the green concrete itself. The green concrete will manage to reduce the green-house gas emission, conserve the natural resources and reduce the problem on the limited landfills area. The research for sustainability has led to the search for the replacement materials that may replace some of the natural resources. Some of the agricultural waste products such as rice husk, rice husk ash, palm oil shells, wood waste ash and coconut shell have been found useful as replacement alternatives for cement, fine aggregate, coarse aggregate and reinforcing materials. The disposal problem of agricultural wastes in many countries have created chances for the use of agro-waste in the construction sector. However, the research about the structural capacity and its performance is still ongoing. The strength and the durability characteristics of rice husk concrete have been widely studied but its suitability to be used as a structural concrete is still in detail study and questionable. This study presents the structural performances and behavior of reinforced concrete beam which using rice husk as a partial replacement of fine aggregate. The experimental works have been conducted involving nine reinforced rice husk concrete beams of dimension 150 mm x 300 mm x 1500 mm. There are three controlled beams with 0 % replacement and another six beams with 10 % and 12 % replacement. The data presented in this paper include the moment capacity, deflection characteristics, cracking behavior and the ultimate load that can resist by the rectangular beam made of rice husk concrete. The main focus of this study is to test on the structural capacity of rectangular beam made up of rice husk concrete under the flexural test.